Ultra-High-Frequency Ultrasound Mapping of the Superficial Circumflex Iliac and Superficial Inferior Epigastric Vessels: An Anatomical Study - Spencer Chia-Hao Kuo; Ryo Karakawa; Hirofumi Imai; Shintaro Kagimoto; Yukio Seki; Nobuko Suesada; Hidehiko Yoshimatsu; Tomoyuki Yano (Diagnostics)
Background: The superficial vessel system in the lower abdomen, including the superficial circumflex iliac artery (SCIA) and superficial inferior epigastric artery (SIEA), is widely used in reconstructive microsurgery. Preoperative ultrasonography, particularly ultra-high-frequency ultrasound (UHFUS), enhances surgical planning by providing high-resolution imaging. This study aimed to utilize UHFUS to examine the SCIA, SCIV, SIEA, and SIEV for reconstructive surgery planning. Methods: This prospective study included 25 patients undergoing free DIEP flap breast reconstruction. Patients with horizontal lower abdominal scars were excluded. Preoperative UHFUS, using a 48 MHz transducer, was performed to map and measure the superficial branch of SCIA (sSCIA), SCIV, SIEA, and SIEV. The vessel location, diameter, depth, and course were documented and analyzed. Results: Twenty-five female patients (50 hemiabdomens) aged 41 to 66 were included. The mean BMI was 21.6 kg/m2 (range: 18.4–30.4 kg/m2). At the ASIS level, the mean diameter of the sSCIA, SIEA, SCIV, and SIEV were 0.76 mm, 0.63 mm, 1.72 mm, and 2.18 mm, respectively. A superior lateral pedicle course was observed in 98% of the sSCIA. All patients had at least one detectable superficial artery, with 96% showing detectable arteries on both sides of the lower abdomen. Conclusions: UHFUS effectively maps superficial vessels in the lower abdomen for reconstructive surgery. The SCIA and SCIV are reliably detectable, while the SIEA is less consistently identified. UHFUS enhances flap design by providing precise vessel localization and sizing, leading to safer and more efficient surgeries.